Pengaruh Kemampuan Personal, Program Pelatihan, Ekspektasi Kinerja dan Pemanfaatan Teknologi terhadap Efektivitas Sistem Informasi Akuntansi pada BUMDES Se-Kecamatan Kubutambahan - Ni Kadek Antari Widindasari; I Putu Julianto (Jurnal Ilmiah Akuntansi dan Humanika, 2022)
This study aims to determine the effect of personal abilities, training programs, performance expectations and utilization of technology on the effectiveness of accounting information systems. The theory used in this research is Theory of Planned Behavior (TPB). The population in this study were all BUMDes in Kubutambahan District. The sampling method used is census method and gets a sample of 39 respondents. The data analysis technique used is multiple linear regression analysis with the help of SPSS 24.0 for Windows. The results showed that personal abilities, training programs, performance expectations and utilization of technology had a positive effect on the effectiveness of accounting information systems